2018
DOI: 10.1039/c7lc01187c
|View full text |Cite
|
Sign up to set email alerts
|

Engineering reaction–diffusion networks with properties of neural tissue

Abstract: We present an experimental system of networks of coupled non-linear chemical reactors, which we theoretically model within a reaction-diffusion framework. The networks consist of patterned arrays of diffusively coupled nanoliter-scale reactors containing the Belousov-Zhabotinsky (BZ) reaction. Microfluidic fabrication techniques are developed that provide the ability to vary the network topology and the reactor coupling strength and offer the freedom to choose whether an arbitrary reactor is inhibitory or exci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 45 publications
0
40
0
Order By: Relevance
“…Despite recent successes in the design and engineering of 3D shape-programmable soft materials, such materials are not presently suitable for so-called soft robotics due to a lack of autonomous and spatiotemporally controlled mechanical function. Living organisms 70 rely on the integration of two types of soft tissue functionality: neural control for signal processing and musculature for actuation motion. Advances in designing microfluidic chemical oscillator networks with the capability of regulating spatiotemporal signals 71,72 are critical to developing actuating/responsive soft materials.…”
Section: Successesmentioning
confidence: 99%
“…Despite recent successes in the design and engineering of 3D shape-programmable soft materials, such materials are not presently suitable for so-called soft robotics due to a lack of autonomous and spatiotemporally controlled mechanical function. Living organisms 70 rely on the integration of two types of soft tissue functionality: neural control for signal processing and musculature for actuation motion. Advances in designing microfluidic chemical oscillator networks with the capability of regulating spatiotemporal signals 71,72 are critical to developing actuating/responsive soft materials.…”
Section: Successesmentioning
confidence: 99%
“…In the early 2000s, the first-ever excitable chemical controller mounted on-board a wheeled robot was constructed and tested under experimental laboratory conditions [20,45,87], and also a robotic hand was interfaced and controlled using BZ medium [128] (figure 11h). Litschel et al [155] showed that by linking micro-reactors with BZ and establishing excitation and inhibitory connections between the neighbouring reactors, it is possible to generate travelling patterns of oscillatory activity resembling the neural locomotive patterns.…”
Section: Reaction-diffusion Computersmentioning
confidence: 99%
“…Processes such as morphogenesis are regulated in part by signalling cues associated with chemical gradients, and mimicking rudimentary aspects of this process in synthetic protocells could provide a step towards the spontaneous physical and chemical differentiation of protocell consortia into multimodal populations of different types of artificial cells. In this regard, recent studies have used chemical gradients and reaction-diffusion systems for the structuring of matter and materials 39,40 , operation of chemical networks 41,42 , programming of artificial cells 43,44 and control of signalling and differentiation in emulsion-based multi-compartmentalized gene circuits 45 . Here, we use chemical gradients comprising unidirectional or counter-directional flows of artificial morphogens to induce spatial and functional differentiation in immobilized protocell arrays consisting of several thousands of initially identical membrane-free coacervate micro-droplets.…”
Section: Introductionmentioning
confidence: 99%